Argentina : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Argentina. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Argentina's government has made important progress in restoring integrity and transparency in public sector operations. These policy changes have put the economy on a stronger footing and corrected many of the most urgent macroeconomic imbalances. Private consumption strengthened in 2017, supported by greater real wages and buoyant credit growth. With stronger domestic demand, the trade surplus turned into a deficit and the current account deficit increased. Annual inflation has declined from its peak in 2016, but remained relatively resilient and inflation expectations moved up, prompting the central bank to raise interest rates. Going forward, GDP growth is expected to consolidate, inflation inertia will slowly subside, and the fiscal deficit will gradually fall.